Surgical cut down for vascular access with conscious sedation for transcatheter aortic valve replacement: the best of both worlds?. (2nd April 2018) - Cardounel, Arturo; Gleason, Thomas G; Lee, Joon S; Schindler, John T; Kliner, Dustin; Navid, Forozan; Bianco, Valentino; Sultan, Ibrahim
Abstract: OBJECTIVES: Despite the established efficacy of transcatheter aortic valve replacement for aortic valve replacement, vascular complications remain a major cause of procedural morbidity and mortality. In this study, we evaluate the use of femoral artery cut down with conscious sedation and report outcomes and complications associated with this approach. METHODS: Our study included 282 patients undergoing transcatheter aortic valve replacement with conscious sedation and surgical cut down for femoral access between 2015 and 2017. Data were prospectively recorded in the local institutional database and were retrospectively accessed. Descriptive statistics are presented, and a Kaplan–Meier time-to-event plot was used to estimate 1-year survival. RESULTS: The mean age of the patients was 82.7 ± 7.31 years and consisted of 146 (52%) women. Echocardiographic data demonstrated a severe aortic stenosis with a mean area of 0.65 ± 0.16 cm 2 and a mean gradient of 48.9 ± 13.3 mmHg. STS-PROM for the cohort was 7.2%, representing an intermediate risk group. Six (2.2%) patients died within 30 days after transcatheter aortic valve replacement. Major vascular complications occurred in 2 (0.7%) patients and minor vascular complications occurred in 6 (2.2%) patients in our cohort. Wound complications were observed in 2 (0.7%) patients. CONCLUSIONS: We demonstrate that the use of conscious sedation and surgical cut down for femoral arterial access resulted in a major vascular complication rate of less than 1% and low in-hospital mortality rates without any significant increase in wound complications.